Potential of natural flavonols and flavanones in the treatment of ulcerative colitis - Li, Cailan; Tang, Ying; Ye, Yonghao; Zuo, Manhua; Lu, Qiang (Frontiers in Pharmacology, 2023)
Ulcerative colitis (UC) is an inflammatory bowel disease generally characterized by chronic, persistent, recurrent, and non-specific ulcers of the intestine. Its main clinical manifestations include abdominal pain, diarrhea, and bloody stools. This disease is difficult to cure and even carries the risk of canceration. It has been listed as a modern refractory disease by the World Health Organization. Though a large amount of drugs are available for the inhibition of UC, the conventional treatment such as aminosalicylic acids, glucocorticoids, immunosuppressors, and biological agents possess certain limitations and serious side effects. Therefore, it is urgently needed for safe and effective drugs of UC, and natural-derived flavonols and flavanones showed tremendous potential. The present study concentrated on the progress of natural-derived flavonols and flavanones from edible and pharmaceutical plants for the remedy of UC over the last two decades. The potential pharmaceutical of natural-derived flavonols and flavanones against UC were closely connected with the modulation of gut microflora, gut barrier function, inflammatory reactions, oxidative stress, and apoptosis. The excellent efficacy and safety of natural flavonols and flavanones make them prospective drug candidates for UC suppression.